ANALISIS JOB EVALUATION SEBAGAI DASAR STRUKTUR KOMPENSASI UKM XYZ DI BIDANG JASA PEST CONTROL - Rosvita Nurlaeli; Salsabila Nasywa Prawira; Tamaka Tariska Bren; Dien Mustika Ardini Adham; Fany Rahmadani; Maharani Azzura (Jurnal Pijar, 2026)
The lack of structured compensation systems remains a common issue among small and medium-sized enterprises (SMEs), leading to subjective salary determination and potential internal inequity. This study aims to analyze the relative value of jobs as a basis for developing an objective and proportional compensation structure at UKM XYZ, a pest control service company. This research adopts a quantitative approach using a point-factor job evaluation method through the application of the eckenrode, adhered, and overlapping methods. Data were collected through interviews, documentation studies, and questionnaires on compensable factor weighting involving company management. The selected compensable factors include formal education, technical competence, responsibility, and working conditions, which reflect the characteristics of service-based operations.The results indicate that formal education and technical competence are the most influential factors in determining job value. The evaluation reveals significant differences across positions, with the Chief Executive Officer (CEO) obtaining the highest score (805 points) and the technician position the lowest (302 points). Furthermore, the overlapping method produces a more moderate and financially feasible compensation structure compared to other methods. These findings demonstrate that compensable factor-based job evaluation enhances the objectivity and proportionality of compensation structures, thereby supporting the achievement of internal equity and more effective human resource management practices in SMEs.